If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + h = 54 Solving 10 + h = 54 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + h = 54 + -10 Combine like terms: 10 + -10 = 0 0 + h = 54 + -10 h = 54 + -10 Combine like terms: 54 + -10 = 44 h = 44 Simplifying h = 44
| -(3-2N)+7N=(N+3)3 | | -6(x-12)+2(x+2)=x-9 | | -6(6y+2)-(-5y-8)=2 | | 1.96=r^2+2r+1 | | -4+2n+16=n+7 | | 1x-2(x+10)=12 | | 7x-9=-4x+90 | | 3(x+5)=3x | | 12*n=12*6 | | -(3-2N)+7N=(N+3) | | 18a-22=-4(1-6a) | | N*1=2 | | 50-6x=-46 | | -5b+24=-8b(b-6)+6b | | 2.5g-14=5 | | 9y^2-72y-81=0 | | x^2+2x+1=11 | | 7+4x=24 | | x^2+40x+384=0 | | 4y+7=6y+14 | | 7+3X=-15 | | -(4x-3)=x+6 | | 4x^2+15x-2.5=0 | | -8*4-6= | | 4x-3=x+6 | | -2=-4x-6x | | 4(3r-2)=3(r+7) | | 7+3x=-22 | | 2-6-4= | | (8x-10)+(8x-10)=6x+6x | | a(-10)-8=-24 | | -3(2x-4)+4x=-34 |